Unusual site of formation of brachiocephalic vein along with multiple venous anomalies in neck and its clinical importance - Rashmoni Jana (Wolters Kluwer Medknow Publications, 2014)
Neck veins are important for various diagnostic, therapeutic and experimental procedures. So knowledge of their anatomical variation is also important. The author reports an unusual site of formation of brachiocephalic vein with multiple venous anomalies in the neck. A rare site of formation of the right brachiocephalic vein was found at the middle of neck under the right sternocleido mastoid muscle by union of right internal jugular and subclavian vein. Another observation was of facial, lingual and superior thyroid veins joined together and formed a common vein over the sternocleidomastoid muscle that drained into the external jugular vein. This unusual course of brachiocephalic vein and aberrant drainage of facial, lingual and superior thyroid veins may cause unusual bleeding during surgeries and invasive procedures. So clinicians should be aware of these variations of major neck veins to avoid complications.